Gereja Katolik dan Pengentasan Pengangguran Pemuda di Era Bonus Demografi - Patricia, Florentina; Olot, Constantine; Steven, Dieler (Studia Philosophica et Theologica, 2024)
Youth unemployment in Indonesia remains notably high at 9.25%, posing a potential threat to the optimal utilization of the demographic dividend anticipated to peak by 2030. This research seeks to explore how the Catholic Church can contribute to addressing youth unemployment during this critical period. By employing the theoretical framework of Catholic social teaching—focusing on the principles of human dignity, solidarity, and integral justice—the study examines the Church's role, potential, and concrete opportunities in mitigating youth unemployment, and provides recommendations for key programs. A qualitative approach is used, involving a literature review of Catholic social teaching documents and analysis of secondary data. The study's findings suggest that the Catholic Church holds strategic potential through its extensive network of parishes and institutions to assist in resolving the youth unemployment issue. Suggested priority programs include skills training, educational scholarships, job fairs, the establishment of youth empowerment institutions, vocational schools, research centers, and business incubators. Effective cross-sector collaboration is crucial to ensuring that these Church-initiated programs function efficiently and offer long- term benefits to Indonesian youth, helping them seize the opportunities presented by the 2030 demographic bonus. This research adds to the understanding of the potential contributions of religious institutions in addressing contemporary socio-economic challenges and opens avenues for further study on the intersection of religion, public policy, and economic development within the framework of Indonesia‘s demographic dividend.